Tau Structures - Avila, Jesus; Jiménez, Juan S.; Sayas, Carmen L.; Bolós, Marta; Zabala, Juan C.; Rivas, Germán; Hernández, Felix (Frontiers in Aging Neuroscience, 2016)
Tau is a microtubule-associated protein that plays an important role in axonal stabilization, neuronal development, and neuronal polarity. In this review, we focus on the primary, secondary, tertiary and quaternary tau structures. We describe the structure of tau from its specific residues until its conformation in dimers, oligomers and larger polymers in physiological and pathological situations.